EFFECTIVENESS AND ADVANTAGES OF ENDOSCOPIC TREATMENT METHODS FOR COMMON BILE DUCT OBSTRUCTIONS - Yusupova Shaxnozaxon Abdikarim qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Advantages and clinical results of endoscopic treatment of obstructive diseases of the common bile duct. The study studied the results of the treatment process in patients who underwent endoscopic retrograde cholangiopancreatography (ERCP), sphincterotomy, stone extraction and stenting. The data obtained showed that endoscopic approaches are characterized by low traumatism, short rehabilitation period and low complication rate. Endoscopic procedures provided high clinical effectiveness in restoring bile duct patency, reducing pain syndrome and normalizing liver function in patients. According to the results of the study, endoscopic methods can be recognized as a preferable, safe and cost-effective approach in modern surgical practice compared to traditional open operations.